Avaliação do material osteológico de boto-vermelho na Coleção de Mamíferos Aquáticos do INPA: análise da distribuição geográfica e diversidade morfológica dos exemplares - Lemos, Nájla Vitória Noronha (Brasil, 2025)
The present study reviews the collection of Inia spp. from the Aquatic Mammal Collection of the National Institute of Amazonian Research (INPA). The research aimed to evaluate the skeletal material of these animals, recording the dry-preserved skeletons and verifying information about the origin, age class, and sex of the individuals. A table was created containing data for each analyzed individual and their respective metadata along with a map of the geographical distribution of the specimens. Each skeleton was examined individually, emphasizing the condition of the skull, mandible, and other bones. The skulls and mandibles were measured for length to enable future comparative analyses between species. The species I. geoffrensis was the most represented in the collection (73,8%), which was found to be in good condition. Most specimens belonged to the adult age class, followed by subadults, juveniles, and calves, offering suitable representation for studies on ontogeny. The geographic distribution analysis revealed that some individuals were collected outside the known distribution areas of the species, suggesting the need for taxonomic revision supported by genetic analysis to ensure accurate identification. This work highlights the importance of careful curation in scientific collections, as well as updating detailed data and records. The Inia spp. collection is established as a valuable tool for future studies, contributing significantly to the conservation and understanding of species of the Amazon River Dolphin.